(untitled) (Research, Society and Development, 2021)
Objective: the objective proposed in this research is to map clinical studies that evaluated the possible benefits of immunomodulatory nutritional Therapy in cancer patients who underwent gastrointestinal surgeries. Method: this is a study protocol of the lotecoping review proposed by Joanna Brigges Intitute. Studies were reviewed in the languages: English and Portuguese, the database selected for the search was, Latin American and Caribbean Literature in Health Sciences (LILACS), MEDELINE/PUBMED and gray literature, the study protocol is registered in the Open platform Science Framework (OSF), under registration osf.io/ef7z9 and doi 10.17605/OSF.IO/YSHF3. Expected Results: A mapping of studies that will assess the clinical outcome of cancer patients who received immunomodulatory nutritional therapy in the perioperative period of gastrointestinal surgery. Conclusion: It is expected that this scope review can find evidence that proves possible benefits presented with immunomodulatory nutritional therapy in cancer patients.